Sixteen Ani Campaigns by Nikolai Marr: The Representativeness of Photographic Documents in the Archival Collection of IHMC RAS - Medvedeva, Maria V. (Actual Problems of Theory and History of Art, 2023)
From 1892 to 1917, sixteen archaeological expeditions led by the Orientalist and archaeologist Nikolai Marr took place in Ani, a unique medieval architectural and archaeological complex that holds an important place in the history of world culture. The expedition members studied Ani churches, including their monumental paintings and decoration elements, fortress architecture, dwellings, ancient inscriptions, and objects of material culture. Years of work have resulted in the accumulation of numerous valuable documents, including diaries and field reports, drawings and photographs. Most of these materials disappeared in 1918; however, the archive at the Institute for the History of Material Culture RAS has preserved some of the documents recording the work carried out in Ani from 1892 till 1917. These include expedition photographs which are of great importance. They are preserved in the collection of the Imperial Archaeological Commission, in the personal collections of Nikolai Marr and the members of the expedition. The photographs portray the landscapes, architecture and monumental painting of Ani, surrounding monasteries, as well as the process of archaeological and restoration work undertaken in different years, the interiors of the Ani Museum and the participants in the expedition. Several photographs still remain unpublished. The most significant photographic collection relates to the first two years of fieldwork. The systematization and introduction of these photographs, together with the analysis of publications and field notes, will provide an opportunity to reconstruct the history of many-years of research in Ani in more detail. This archival material has become particularly important in recent years with the resumption of restoration work and the reopening of the museum in Ani. The study was supported by the Russian Science Foundation (Project No. 22-18-00354, https://rscf.ru/project/22-18-00354 “The Architecture and monumental art of Ani as a phenomenon of world artistic culture. Making of the metropolitan school of Armenian architecture of the 10th–14th centuries”), at the National Research Moscow State University of Civil Engineering.